Uso de alineadores para la resolución de apiñamiento en maloclusión Clase II. Reporte de caso - Hurtado Salazar , Susana Mitchell (2025)
This case report presents the application of clear aligners to correct crowding in a patient with Class II malocclusion. Traditionally, orthodontics has been used fixed appliances to treat these malocclusions, but technological advances have allowed the use of aligners as a functional and aesthetic alternative. This study describes the case of a 26-year-old female patient who received treatment with aligners in the lower jaw. The treatment focused on correcting the lower crowding, improving the gear of the teeth on the left side, correcting the Class II canine relationship on the same side, and adjusting the inclination of the lower left second molar. The case demonstrates the effectiveness of aligners in managing crowding and improving occlusal gear.